Reproductive Health Problems in Adolescent Female Garment Workers of Dhaka City (Bangladesh Medical Journal, 2014)
This cross sectional study was carried out at a selected garment industry in Dhaka city during the period from July 2010 to December, 2010. The study was conducted to find out the pattern of reproductive health problems among the adolescent female garment workers. A total of 100 adolescent female workers were included in the study purposively. Data was collected by using a semi-structured questionnaire. Majority respondents were in between 16 -18 years of age group and 80% of them were illiterate and up to primary level with equal proportion. Most of the female adolescents were unmarried and Muslim by religion. Majority of the adolescents (68%) suffered from menstruation problems like dysmenorrhoea (42%), menorrhogea (11%), irregular bleeding (8%) and oligomenorrhoea (7%). More than one third (39%) of the workers had genital tract problems and majority (61%) had no problems. Majority of them (65%) were practicing hygienic measures during menstruation. The study findings recommended for wide scale survey to identify common reproductive health problems among the female adolescent garment workers. It also suggests for formulation and implementation of necessary measures to improve reproductive health status of adolescent female workers in Dhaka city as well as in Bangladesh. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18777 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 25-27